2005
DOI: 10.1111/j.1708-8208.2005.tb00053.x
|View full text |Cite
|
Sign up to set email alerts
|

An Antibacterial Surface on Dental Implants, Based on the Photocatalytic Bactericidal Effect

Abstract: The bactericidal effect of the TiO(2) photocatalyst is of great use for sterilizing the contaminated surface of dental implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 33 publications
1
74
0
Order By: Relevance
“…Ohko et al (2001) have found that silicone catheters coated with a thin layer of TiO 2 can be decontaminated using UV radiation of low intensity. Similar bactericidal effects were also observed in experiments on the sterilization of contaminated dental implants coated with titanium dioxide (Suketa et al 2005). Bactericidal properties of photocatalytic coatings have been used in filters cleaning the air (Lopez and Jacoby 2002) and in installations for water decontamination (Ireland et al 1993, Alrousan et al 2009, Chong et al 2010.…”
Section: Discussionsupporting
confidence: 50%
“…Ohko et al (2001) have found that silicone catheters coated with a thin layer of TiO 2 can be decontaminated using UV radiation of low intensity. Similar bactericidal effects were also observed in experiments on the sterilization of contaminated dental implants coated with titanium dioxide (Suketa et al 2005). Bactericidal properties of photocatalytic coatings have been used in filters cleaning the air (Lopez and Jacoby 2002) and in installations for water decontamination (Ireland et al 1993, Alrousan et al 2009, Chong et al 2010.…”
Section: Discussionsupporting
confidence: 50%
“…The TiO 2 layer conferred photocatalytic bactericidal effect against S. aureus under UVA irradiation. The bactericidal effects of TiO 2 under UV-light irradiation is particularly useful for sterilizing the contaminated surface of dental implants as reported by Suketa et al (112). The authors used a plasma source ion implantation to deposit a layer of TiO 2 onto metallic titanium and tested the photobactericidal effectiveness of the resulting surfaces on Actinobacillus actinomycetemcomitans and Fusobacterium nucleatum, two microorganisms responsible for infections of the oral cavity.…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…In applying the photocatalytic bactericidal properties of titania, an on-demand feature for decontamination can be added to biomedical surfaces, and is of particular interest for percutaneous implants and devices. A number of studies have been devoted to this matter and have shown promising results [4,11,[34][35][36][37], but further research is needed to improve efficiency and avoid adverse effects of UV light on healthy tissue, etc.…”
Section: Discussionmentioning
confidence: 99%